İddianamenin iadesi ile ilgili sorunlar ve çözüm önerileri - Arıtürk, Ramazan (Türkiye Adalet Akademisi, 2022)
Soruşturma evresinde delillerin yeterli seviyede toplanmaması ve iddianamede bulunması gerekli unsurlara yer verilmemesi gibi nedenlerle soruşturmanın tamamlanamaması veya etkin soruşturma yapılamaması kovuşturma evresinin uzamasına, adaletin geç tesis edilmesine ve sonuç olarak kişinin lekelenmeme hakkının ihlaline yol açmaktadır. Bu konulardaki rahatsızlıkları gidermek amacıyla kanun koyucu 5271 sayılı Ceza Muhakemeleri Kanunu ile birlikte iddianamenin iadesi kurumunu ceza muhakemesine kazandırmıştır. Bu çalışmada, iddianamenin iadesi kurumunun karşılaştırmalı hukukla birlikte niteliği ve uygulamadaki karşılığı, eksikleri ile birlikte değerlendirilecek ve bu eksikliklerin giderilmesinden sonra söz konusu kurumun bireylerin hak ve özgürlüklerinin korunması konusunda ne kadar önemli olduğu önerilerimiz doğrultusunda ortaya koyulacaktır.

Completion of the investigation due to reasons such as insufficient collection of evidence during the investigation phase and not including the elements required to be included in the indictment lead to an inability to conduct an effective investigation, prolongation of the prosecution phase, delay in the establishment of justice and, consequently, a violation of the person’s right not to be tainted. In order to eliminate the discomforts in these matters, the legislator brought the institution of return of indictment to the criminal procedure with the Criminal Procedure Law No. 5271. In this study, the institution of the return of the indictment will be evaluated together with its shortcomings in the light of the comparative law, its nature and its provision in practice, and after these deficiencies are eliminated, the importance of the institution in question in terms of protecting the rights and freedoms of individuals will be revealed in line with our suggestions.
Problems and solution recommendations on return of ındictment and ınitiation of public prosecution
Keywords: İddianamenin iadesi; Kovuşturma; Soruşturma; Lekelenmeme hakkı; Return of indictment; Right to prosecution; Investigation; Right not to be tainted